Get the answers you've been searching for with IDNLearn.com. Join our platform to receive prompt and accurate responses from experienced professionals in various fields.
Sagot :
To find the sum of the series
[tex]\[ \sum_{k=1}^4(3k)^2, \][/tex]
let's break it down step by step.
1. We start by substituting [tex]\( k \)[/tex] with 1, 2, 3, and 4 into the expression [tex]\( (3k)^2 \)[/tex].
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ (3 \cdot 1)^2 = 3^2 = 9. \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ (3 \cdot 2)^2 = 6^2 = 36. \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ (3 \cdot 3)^2 = 9^2 = 81. \][/tex]
5. For [tex]\( k = 4 \)[/tex]:
[tex]\[ (3 \cdot 4)^2 = 12^2 = 144. \][/tex]
6. Now, we need to add up all these values.
[tex]\[ 9 + 36 + 81 + 144. \][/tex]
7. Let's sum these values step by step:
[tex]\[ 9 + 36 = 45, \][/tex]
[tex]\[ 45 + 81 = 126, \][/tex]
[tex]\[ 126 + 144 = 270. \][/tex]
Therefore, the sum of the series is
[tex]\[ \boxed{270}. \][/tex]
[tex]\[ \sum_{k=1}^4(3k)^2, \][/tex]
let's break it down step by step.
1. We start by substituting [tex]\( k \)[/tex] with 1, 2, 3, and 4 into the expression [tex]\( (3k)^2 \)[/tex].
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ (3 \cdot 1)^2 = 3^2 = 9. \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ (3 \cdot 2)^2 = 6^2 = 36. \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ (3 \cdot 3)^2 = 9^2 = 81. \][/tex]
5. For [tex]\( k = 4 \)[/tex]:
[tex]\[ (3 \cdot 4)^2 = 12^2 = 144. \][/tex]
6. Now, we need to add up all these values.
[tex]\[ 9 + 36 + 81 + 144. \][/tex]
7. Let's sum these values step by step:
[tex]\[ 9 + 36 = 45, \][/tex]
[tex]\[ 45 + 81 = 126, \][/tex]
[tex]\[ 126 + 144 = 270. \][/tex]
Therefore, the sum of the series is
[tex]\[ \boxed{270}. \][/tex]
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and see you next time for more reliable information.